AMEND study protocol: a case–control study to assess the long-term impact of invasive meningococcal disease in Australian adolescents and young adults. Issue 12 (29th December 2019) - Marshall, Helen; McMillan, Mark; Wang, Bing; Booy, Robert; Afzali, Hossein; Buttery, Jim; Blyth, Christopher C; Richmond, Peter; Shaw, David; Gordon, David; Barton, Belinda
Abstract : Introduction: Invasive meningococcal disease (IMD) primarily causes disease in young children and adolescents and can cause long-term disability. Many countries are considering implementation of meningococcal B and/or meningococcal ACWY vaccines to control meningococcal disease. Estimating the cost-effectiveness of meningococcal vaccine programme is hampered due to a lack of good quality costing and burden of disease data. This study aims to address this evidence gap by assessing the clinical, physical, neurocognitive, economic and societal impact of IMD on adolescents and young adults. Methods and analysis: A case–control study of 64 participants with confirmed IMD (15–24 years 11 months at time of disease) and 64 control participants (17–34 years 11 months) will be conducted in Australia from 2016 to 2020. All participants will undergo a neurocognitive assessment, full medical examination, pure tone audiometry assessment and complete quality of life and behavioural questionnaires. Meningococcal cases will be assessed 2–10 years posthospitalisation and a subset of cases will be interviewed to explore in depth their experiences of IMD and its impact on their life. Primary outcome measures include general intellectual functioning from the Wechsler Adult Intelligence Scale and overall quality of life from the Health Utilities Index. Secondary outcome measures include academic achievement, executive functioning, behaviour, hearing, psychological and physical functioning. Outcome measures will be compared between cases and controls using independent t-tests or ORs, or if any significant confounders are identified, adjusted analyses (analysis of covariance or adjusted ORs) will be conducted. Thematic analysis will be used to analyse transcribed interviews and a costing model will be used to project lifetime costs. Ethics and dissemination: The Adolescent MENingococcal Disease (AMEND) study has been approved by the Human Research Ethics Committee of the Women's and Children's Health Network (HREC/14/WCHN/024). The results will be disseminated via peer-reviewed publications, conference presentations, study participants, and meningococcal and meningitis foundations. Trial registration number: NCT03798574 .